Social World in Photography - a Proposal of a Workshop on the Research Strategies with the Use of Photographs - Golonka, Joanna; Pryszmont-Ciesielska, Martyna (INSTED: Interdisciplinary Studies in Education & Society, 2012)
Teaching methodology of social research in pedagogic programmes we have experienced students? great interest in the possibilities of using photography and photographing practices in the research projects carried out by them. Also the personal interest in photography and the attempts of using it in our research were a reason for us deciding to prepare a project of workshops devoted to the research strategies that use photography. Our aim was to make the most of students? individual interests and their conscious transfer into the space of research activities. Simultaneously, the suggested classes were also a specific didactic provocation. This article discusses our project, which was carried out in the summer semester of the academic year of 2010/2011.